1996
DOI: 10.1007/bf00146348
|View full text |Cite
|
Sign up to set email alerts
|

Long-term behavior of latitudinal cosmic-ray gradients

Abstract: We have used neutron monitor data covering a wide range of energy over a period of 22 years , as well as sea-level multidirectional meson telescope data from Nagoya to examine the latitude effect of solar diurnal vectors and its dependence on the polarity of interplanetary magnetic field (IMF). By sorting the daily cosmic-ray data according to whether the IMF is toward (T) or away (A) from the Sun, the annual mean solar diurnal variations (amplitude and phase) for the T and A days were determined separately. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Thus, the change in the phase of tri-diurnal anisotropy of CR intensity has been found quite significant. It is clear that there exist a 11 year type of variation in third harmonics of CR intensity on QD due to the variation of solar activity [El Borie et al 1995b]. The polarity dependence of the phase shift change has been interpreted as a result due to the change of CR density distribution in space caused by the difference of CR drift motion in the positive and negative polarity state [Munakata et …”
Section: Resultsmentioning
confidence: 99%
“…Thus, the change in the phase of tri-diurnal anisotropy of CR intensity has been found quite significant. It is clear that there exist a 11 year type of variation in third harmonics of CR intensity on QD due to the variation of solar activity [El Borie et al 1995b]. The polarity dependence of the phase shift change has been interpreted as a result due to the change of CR density distribution in space caused by the difference of CR drift motion in the positive and negative polarity state [Munakata et …”
Section: Resultsmentioning
confidence: 99%
“…The N-S asymmetry was found in many parameters related to the interplanetary medium [3,4,7,10]. Results of El-Borie [7] and El-Borie et al [6] showed that the dependence of N-S asymmetry of field magnitude (B) upon the interplanetary solar polarities is statistically insignificant. There is no clear indication for the presence of N-S asymmetry over the solar cycles.…”
Section: Introductionmentioning
confidence: 96%
“…The unequal distribution of various interplanetary plasma and solar parameters between the north and south hemispheres of the Sun (north-south asymmetry) is well known for many years and has been studied by many authors (e.g., [1][2][3][4][5][6][7][8][9][10]). Most interplanetary plasma parameters are highly variable on time scales ranging from minutes to the solar activity cycle and vary with heliographic latitude and longitude [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The N-S asymmetries in the interplanetary plasma, solar indices and the cosmicray intensities between the northern and southern sectors, with respect to the heliospheric neutral sheet, have been studied [1][2][3][4][5][6][7][8][9]. The N-S asymmetry distributions of major flares, sunspot areas were independent on the 11 yr solar cycle [5,6].…”
Section: Introductionmentioning
confidence: 99%